2017
DOI: 10.1039/c7fo00355b
|View full text |Cite
|
Sign up to set email alerts
|

The hepatoprotective effect of the probiotic Clostridium butyricum against carbon tetrachloride-induced acute liver damage in mice

Abstract: Previous studies have revealed that the probiotic Clostridium butyricum (C. butyricum) can attenuate cirrhosis in chronic non-alcoholic liver disease. However, the effects of C. butyricum on acute liver injury (ALI) remain unclear. Therefore, the present study aims to examine the hepatoprotective effects and the underlying mechanisms employed by C. butyricum in a carbon tetrachloride (CCl)-induced ALI murine model. Here, we evaluated the survival rate and the levels of alanine aminotransferase (ALT), aspartate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
64
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(74 citation statements)
references
References 42 publications
10
64
0
Order By: Relevance
“…57,58 This binding causes the downstream activation of HO-1. 59 The present study stated enhanced nuclear accumulation of Nrf2 by triptolide in the case of reperfused hepatic tissue. In addition to this, HO-1 activity was upregulated by treatment with Met and Lut.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…57,58 This binding causes the downstream activation of HO-1. 59 The present study stated enhanced nuclear accumulation of Nrf2 by triptolide in the case of reperfused hepatic tissue. In addition to this, HO-1 activity was upregulated by treatment with Met and Lut.…”
Section: Discussionsupporting
confidence: 60%
“…Nrf2 then translocates to the nucleus and binds to the ARE . This binding causes the downstream activation of HO‐1 . The present study stated enhanced nuclear accumulation of Nrf2 by triptolide in the case of reperfused hepatic tissue.…”
Section: Discussionsupporting
confidence: 55%
“…Previous studies have shown similar results on hepatoprotective of propolis, 24 but only a few studies have attempted to determine the protective role of probiotics on CCl4-induced liver toxicity. 25 As shown in Figure 2, CCl4 caused an increase of serum cholesterol and triglycerides levels (p < 0.01), which was reversed by a pretreatment with PRS or L. acidophilus. This is in agreement with earlier study pointing out that PRS modulates cholesterol levels and protects the cardiovascular system through an anti-inflammatory action.…”
Section: Discussionmentioning
confidence: 83%
“…These two kinds of free radicals can eventually lead to hepatic lesions by attacking polyunsaturated fatty acids in biofilm phospholipids and trigger lipid peroxidation reactions [11]. Based on CCl 4 -induced hepatic injury animal models, the study of the hepatoprotective effect of microorganisms has made some progress [12,13,14]. …”
Section: Introductionmentioning
confidence: 99%